2003
DOI: 10.3748/wjg.v9.i4.688
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a regulable gene therapy vector targeting for hepatocellular carcinoma

Abstract: This recombinant expression vector can be used as a gene therapy vector for HCC. The expression of tumor killing gene will be confined within the site of tumor and the activity of which can be regulated by retinoic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…AFP promoter constructs have been applied in a variety of studies and have been demonstrated to effectively target reporter or therapeutic genes to HCC cells, while avoiding toxicity to normal liver cells. [22][23][24][25] Expression of AFP is regulated by four distinct regulatory elements, including the proximal promoter and three enhancer domains (enhancers I, II, III). In our study, to target NIS gene transfer to hepatoma cells we applied a 2666 bp mouse AFP promoter construct consisting of the basal promoter and enhancer I element, that are known to provide maximal tissue specificity and promoter activity.…”
Section: 16mentioning
confidence: 99%
“…AFP promoter constructs have been applied in a variety of studies and have been demonstrated to effectively target reporter or therapeutic genes to HCC cells, while avoiding toxicity to normal liver cells. [22][23][24][25] Expression of AFP is regulated by four distinct regulatory elements, including the proximal promoter and three enhancer domains (enhancers I, II, III). In our study, to target NIS gene transfer to hepatoma cells we applied a 2666 bp mouse AFP promoter construct consisting of the basal promoter and enhancer I element, that are known to provide maximal tissue specificity and promoter activity.…”
Section: 16mentioning
confidence: 99%
“…In an attempt to develop a system that can also be applied to liver cancer, we searched for a liver cancerspecific promoter and identified several potential liver cancer-specific promoter candidates, including a-fetoprotein (AFP) basic promoter and AFP basic promoter combined with AFP enhancers (eAFP), both of which have already been known for being highly liver cancer specific (Kim and Wang, 2003;Lu et al, 2003;Shi et al, 2004;Suriawinata and Xu, 2004;Lemken et al, 2005;Guan et al, 2006). AFP, produced by the yolk sac and liver, is expressed at high levels during early development in fetus and decreases to a low or undetected level in adults (Abelev and Eraiser, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The size of NPs is important for a favourable cellular uptake. Polycation/DNA gene‐delivery systems mostly enter the cell by endocytosis or pinocytosis, meaning that they have a size requirement of less than 100 nm for maximum endocytosis by non‐specialized cells [16]. Smaller NPs show a higher accumulation in tissues and a prolonged in vivo half‐life due to their avoidable capture by the reticuloendothelial system.…”
Section: Resultsmentioning
confidence: 99%